AUTOMATIC MODELING OF THE SURFACE OF THE SAME SLOPE IN THE ELLIPTICAL PLAN IN AUTOCAD THROUGH THE AUTOLISP LANGUAGE - V A Romanova; Anamariya Thoma (RUDN Journal of Engineering Research, 2016)
Graphical computer modeling is a real possibility of solving problems for the education surfaces the kinematic method. It is due to the availability of computer-aided design, such as MathCad, Mathematika, AutoCad etc. The advantage of AutoCad is the availability of built-in AutoLisp language is functional. Having a wide set of mathematical functions and functions to draw graphical objects, language AutoLisp allows you to write a program to draw the shells of any complexity, in the particular case of shell the same slope in the elliptical plan, with subsequent transfer of results in the AutoCAD environment. The reproduction of objects in slow motion gives you the ability to create mini-movies about the formation of the surfaces. Image graphic creations in three-dimensional space, using the AutoCAD color palette enhances the expressiveness of the image surfaces and their elements.The aim of the study is the possibility of modeling the surface of the same slope in the elliptical plan, carried out by its gradual drawing in slow dynamically creating a mini-film, which allows to represent on the screen the process of formation of the surface.